Prevalence, characteristics, and associated risk factors of drug consumption and chemsex use among individuals attending an STI clinic (EpITs STUDY) - Rosas Cancio-Suárez, Marta; Ron, Raquel; Díaz-Álvarez, Jorge; Martínez-Sanz, Javier; Serrano-Villar, Sergio; Moreno, Santiago; Sánchez-Conde, Matilde (Frontiers in Public Health, 2023)
Sex-related drug consumption and its health-related consequences have gained relevance in the assessment of patients with sexually transmitted infections (STIs), which pose a significant challenge to public health. We aim to assess the prevalence and characteristics of drug consumption and chemsex practices, describe the associated risk factors among general individuals attending an STI clinic, and evaluate the psychological impact associated with these behaviors. We conducted an online anonymous survey offered to patients with a diagnosis of STI in a tertiary hospital in Spain. Data included sociodemographic characteristics, sexual preferences and behavior, and assessment of drug use, chemsex, and psychological and mental health symptoms. Data from 145 subjects was collected, with a higher proportion of cis-gender men (71%), and a median age of 32 years. 64 participants (44%) reported drug use in the last year, with an observed 33.8% prevalence of chemsex consumption. Drug use and chemsex were more frequent among cis-gender men, Men who have Sex with Men (MSM), people living with HIV (PLHIV), and those reporting previous group sex. Poppers and cannabis were the most frequently reported drugs, with a prevalence close to 20% for cocaine, mephedrone, extasis, and GHB. Consequences related to drug use included unpleasant physical sensations, sexual dysfunction, and impaired sexual experience after reduction or drug discontinuation. The prevalence of drug use and chemsex practices are high among patients evaluated for STIs, especially between men, MSM, and subjects practicing group sex. The study highlights the urgent need for targeted interventions on prevention and reduction of their impact on health and social well-being.